2010
DOI: 10.1007/s12562-010-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably high survival rates under dim light conditions in sutchi catfish Pangasianodon hypophthalmus larvae

Abstract: The sutchi catfish Pangasianodon hypophthalmus is an important species for aquaculture in Southeast Asia. However, larvae typically have low survival rates due to their predilection for cannibalism during rearing. This study investigated larval feeding behavior and rearing conditions. The former experiments were performed to elucidate the role of sensory organs in feeding, and the latter experiments examined the effect of dim light on larval rearing and survival rates. Neither lighting conditions (light and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Feeding behaviour of fish larvae is closely related to their sensory organs (Blaxter ; Mukai & Kobayashi , ; Fuiman, Higgs & Poling ; Mukai , ; Mukai, Lang, Sitti Raehanah & Senoo ; Mukai, Tuzan, Lim et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding behaviour of fish larvae is closely related to their sensory organs (Blaxter ; Mukai & Kobayashi , ; Fuiman, Higgs & Poling ; Mukai , ; Mukai, Lang, Sitti Raehanah & Senoo ; Mukai, Tuzan, Lim et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…). Moreover, Mukai () also reported that sutchi catfish show survival rates three times higher under dim conditions (0.1 lx) than those under brighter conditions (100 lx). Mukai () postulated that this was a result of the less aggressive behaviour of catfish under dim conditions; however, there is no quantitative data to support this claim.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cannibalism can cause heavy losses during the early stages of cultured fish especially river catfish. The growth performance of river catfish has been manipulated by feeding frequency, stocking density and light intensity (Mukai, ; Sayeed, Hossain, Mistry, & Huq, ; Slembrouck, Baras, Subagja, Hung, & Legendre, ). The present was conducted to identify the most ideal tank background colour to further enhance the growth performance, suppress cannibalism and perhaps increase the value of seed of river catfish.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the visual sensitivity and behaviour of fish larvae in their natural habitats, and to determine the optimum illuminating conditions in captivity. There are many studies on visual sensitivity of fish larvae through retinomotor responses (Ali ; Blaxter ; Blaxter ; Blaxter & Staines ; Kawamura ; Neave ; Masuma, Kawamura, Tezuka, Koiso & Namba ) and on feeding behaviour under different light intensities (Blaxter ,b; Mukai , ; Mukai, Tuzan, Lim & Yahaya ). Boeuf and Bail () describe the effect of light intensities on growth of many fish species.…”
Section: Introductionmentioning
confidence: 99%